Perlindungan Hukum Terhadap Pembeli Beritikad Baik dalam Sengketa Kepemilikan Tanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Land ownership disputes are a common legal issue in Indonesia and often disadvantage buyers who act in good faith. A good faith buyer is someone who enters into a transaction based on trust in the seller’s legal ownership without knowledge of any legal defects. This study aims to analyze the forms of legal protection available to good faith buyers in land ownership disputes. The research uses a normative juridical method with a statutory and case approach based on court decisions. The findings show that although the nemo plus iuris principle prioritizes legal ownership, good faith buyers can still obtain legal protection through the principles of justice, good faith, and legal certainty, as recognized in various court rulings. The implications of this research highlight the need for reform in land policy and the proactive role of land deed officials in preventing problematic transactions, ensuring that the rights of good faith buyers are not neglected